2022
DOI: 10.1111/apa.16493
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of early cerebralNIRSin hypoxic ischaemic encephalopathy

Abstract: Aim: To describe early cerebral oxygenation (cSO 2 ) and fractional tissue oxygen extraction (FTOE) values and their evolution over the first days of life in infants with all grades of hypoxic-ischaemic encephalopathy (HIE) and to determine whether cSO 2 and FTOE measured early (6 and 12 h) can predict short-term outcome.Methods: Prospective, observational study of cerebral near-infrared spectroscopy (NIRS) in infants >36 weeks' gestation with HIE. Ten one-hour epochs of cSO 2 and FTOE were extracted for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…This study concluded that a rate of rise between 0.5% and 0.7% per hour is associated with moderate to severe brain injury on MRI at 14 days of life 20. This is further supported by research by Garvey et al,19 who also observed a correlation between rScO 2 and the grade of HIE 19. Infants with moderate HIE had a steeper rate of rise than infants with mild HIE, but a slower rate of rise than infants with severe HIE 19.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…This study concluded that a rate of rise between 0.5% and 0.7% per hour is associated with moderate to severe brain injury on MRI at 14 days of life 20. This is further supported by research by Garvey et al,19 who also observed a correlation between rScO 2 and the grade of HIE 19. Infants with moderate HIE had a steeper rate of rise than infants with mild HIE, but a slower rate of rise than infants with severe HIE 19.…”
Section: Resultssupporting
confidence: 66%
“…20 This is further supported by research by Garvey et al, 19 who also observed a correlation between rScO 2 and the grade of HIE. 19 Infants with moderate HIE had a steeper rate of rise than infants with mild HIE, but a slower rate of rise than infants with severe HIE. 19 Additionally, it was noted that infants with severe HIE exhibit a rate of rise that is almost linear.…”
Section: Cnirs Ability To Screen For Mild Moderate or Severe Hiesupporting
confidence: 54%
See 2 more Smart Citations
“…As a surrogate for cerebral blood flow, the chronologic evolution of rScO2 may be an important bedside measure and further serve as a prognostic tool ( 40 ). While therapeutic hypothermia itself contributes to vasoconstriction and decreased cerebral blood flow, this effect is mitigated by a larger decrease in metabolic demand, subsequently resulting in higher rScO2 and lower fTOE ( 41 , 42 ) ( Figure 5 ). After initiation of cooling, a modest increase in rScO2 is typically seen due to these effects.…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%